Revision of the Swedish species of Neoxorides Clément, 1938 (Ichneumonidae: Poemeniinae) with the description of a new species and an illustrated key to species - Johansson, Niklas; Klopfstein, Seraina (European Journal of Taxonomy, 2020)
Neoxorides Clément, 1938 is a small genus of ichneumonid wasps that develop on wood-boring beetles. We here revise the Western Palaearctic species of the genus, with a special focus on Sweden. A new species, N. striatus Johansson sp. nov. is described. Neoxorides opacus (Kokujev, 1903) stat. rev. is excluded from the synonymy with N. nitens (Gravenhorst, 1829) and reinstated as a valid species. The species is redescribed from European material. Neoxorides kissi (Ulbricht, 1911) is confirmed as a junior synonym of N. opacus. A neotype for N. opacus is designated. New characters to distinguish N. varipes (Holmgren, 1860), N. collaris (Gravenhorst, 1829) and N. montanus Oehlke, 1966 are presented. Almost all of the species treated are supported by DNA-barcoding. An illustrated key to the species occurring in the Western Palaearctic is provided, a prerequisite for making the genus accessible for future ecological and conservation studies.